Food preferences and perceptions of healthy food among primary school children and barrier factors for food selling guideline compliance in Kelantan school canteens - Aziz, Nurulhuda Abd (2018)
Healthy School Canteen Management Guidelines (HSCMG, 2011) has been introduced to encourage selling of nutritious food at schools. However, there are challenges to implement healthy menus at school canteens. Thus, the aim of this study was to investigate the association between healthy food preferences and perceptions among primary school children, and also to discover barrier factors that obstruct school canteen from complying the food selling guidelines under the HSCMG 2011. In Part I study (quantitative study), it examined children’s sociodemographic characteristics, body weight status, food intake patterns, as well as relationship between food preferences and perceptions. Stratified sampling method was applied to select seven schools. A cross-sectional survey was given to 196 primary school children in Kelantan. The modified stacking box method was used to help children ranked a number of foods according to their preferences and perceptions of healthy foods. Then, Food Frequency Questionnaire (FFQ) was used to investigate children food intake patterns. Lastly, Spearman’s Rank-Order Correlation was used to analyse correlation between selected variables. While in Part II study (qualitative study), purposive sampling was applied to recruit six teachers who involved in school canteen management. Semi-structured in-depth interviews were conducted. Part II study used the Atlas.ti 7 for data management. Results from descriptive statistic showed roastedchicken (62.8%) and boiled egg (67.3%) were ranked by majority respondents as most preferable food and the healthiest food, respectively. A total of 56.6% children had ranked steamed sweet potatoes as the least preferred food while 58.2 % children had ranked French fries as the unhealthiest food. There was positive significant correlation between preferences and perceived healthy for steamed bun, steamed rice cake, fried noodles and fried burger beef patty. A negative significant correlation was observed between BMI and steamed bun preferences (rs = -0.153, P<0.05). Conversely, BMI was positively associated with preferences for French fries (rs = 0.150, P<0.05) and fried bread sausage (rs = 0.151, P<0.05). Research finding also discovered eight barrier factors had discouraged compliance of food selling guidelines included lacking of implementation and enforcement, children’s food preferences, low socioeconomic status, profit margin, lacking of effective ways to promote healthy eating, competitive foods sold outside the school, parents' feeding practices and limitations from school caterer. In conclusion, children had the ability to recognise healthy food correctly. However, they still had higher preferences for processed food which is unbalanced diet. Junk food as well as processed food should be banned at school canteen and not just categorized as ‘not recommended’. This study suggests that strict enforcement, effective communication and legislative action is very important in order to ensure implementation and monitoring of food selling guidelines under the HSCMG 2011 was carried out seriously.